The Effects Of Green Products, Price Perception And Attitude On Purchase Intention of Sustainable Fashion - Ardheta, Firza Intan; Shiratina , Aldina (ARE Publisher, 2024)
Objective : The issue of environmental damage caused by clothing garbage accumulation, which highlights the importance of focusing on businesses that prioritize the environment and sustainability, which need to be enhanced in today's economy. This study aims to analyze the effect of Green Products, Price Perceptions, Environmental Attitudes on Buying Interests of Senaleen clothing products. Methodology : The population in this study were Senaleen Instagram followers, who are concerned about the environment and know the Senaleen brand. Sampling method using Purposive Sampling. The data collection method uses a survey method, with a research instrument in the form of a questionnaire. The data analysis method used is Partial Least Square. Finding : Green Products have a positive and significant effect on Purchase Intention. Price Perception has a positive and significant effect on Purchase Intention. Environmental Attitudes do not have a significant effect on Purchase Intention.